Effect of Covid-19 on the Performance of Selected Hotels in Mbarara City. - Mukama, Gad (Kabale University, 2023)
This study was about the effect of COVID-19 on the performance of selected hotels in Mbarara city. The general objective of the study was to find out the effects of COVID-19 on the performance of selected hotels in Mbarara City. Three specific objectives guided the study including; examining the effect of COVID-19 on hotel employees, evaluating the performance of Hotels in Mbarara City, and finding out the relationship between COVID-19 and the performance of Hotels in Mbarara City. The study employed used a descriptive cross-sectional survey design where data was collected across the population at one point in time and a mixed approach was employed. Using a questionnaire research instrument, data was collected from 87 respondents that included the hotel managers and selected workers of Triangle Hotel, Luongo Hotel, Jameson, Agip, and San Diego. The first study examining the effect of COVID-19 on hotel employees revealed that client reeducation was the major effect of COVID-19 that affected visitors to the hotels as revealed by 65% of the respondents. The second study objective about evaluating the performance of Hotels in Mbarara city revealed that before covid-19 pandemic there were stable employees as reflected by 33% responses, during covid-19 pandemic there was client reduction as mentioned by 65% of respondents. The third study objective about the relationship between COVID-19 and the performance of Hotels in Mbarara City revealed that there was an effect mentioning the reduction of salaries as the major relationship between the variables. The study therefore recommended that Hotels in Mbarara city be ready for a post-corona environment. There are different scenarios on when the industry will recover, what new challenges and standards will be imposed, who are more likely to travel which products and services will disappear and transform. Hence the stakeholders especially hotel owners should be able to create different action plans for each scenario to be put into action after recovery.